Better data visualizations : a guide for scholars, researchers, and wonks - Schwabish, Jonathan A. (©2021, 2021)
'Now more than ever, content must be visual if it is to travel far. Readers everywhere are overwhelmed with a flow of data, news, and text. Visuals can cut through the noise and make it easier for readers to recognize and recall information. Yet many researchers were never taught how to present their work visually. This book details essential strategies to create more effective data visualizations. Jonathan Schwabish walks readers through the steps of creating better graphs and how to move beyond simple line, bar, and pie charts. Through more than five hundred examples, he demonstrates the do's and don'ts of data visualization, the principles of visual perception, and how to make subjective style decisions around a chart's design. Schwabish surveys more than eighty visualization types, from histograms to horizon charts, ridgeline plots to choropleth maps, and explains how each has its place in the visual toolkit. It might seem intimidating, but everyone can learn how to create compelling, effective data visualizations. This book will guide you as you define your audience and goals, choose the graph that best fits for your data, and clearly communicate your message'--
Introduction: How I learned to visualize my data -- Visual processing and perceptual rankings -- Five guidelines for better data visualization -- Form and function -- Comparing categories -- Time -- Distribution -- Geospatial -- Relationship -- Part-to-whole -- Qualitative -- Tables -- Developing a data visualization style guide -- Redesigns.
Includes bibliographical references and index.
Nor Izzati Abdul Aziz/IKMAS/izzatina aziz@ukm.edu.my/i-quest/CIP/Ashe
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Information visualization; Visual analytics